Maintaining momentum for conservation: Bighorn sheep as an example - Vernon C. Bleich (Wildlife Society Bulletin, 2018)
ABSTRACT Bighorn sheep (Ovis canadensis) and Dall's sheep (O. dalli) are among the iconic megafauna of North America. Both species generate great public interest and have received much attention from management agencies and conservation groups. Bighorn sheep, however, have suffered far more management setbacks than have their northern congeners and, as a result, have been the beneficiary of aggressive conservation programs. Nevertheless, both species face continuing challenges. Among those challenges are limited preparation of personnel, interagency competition, bureaucratic inertia, confounding legislation, public advocacy (or the lack thereof), political expediency, and interpersonal issues. To foster and maintain momentum for conserving wild sheep, I encourage managers to 1) enhance relationships with nongovernmental organizations, private enterprise, and the media; 2) work more closely with sister agencies to take advantage of opportunities or skillsets; 3) seize opportunities for enhancing conservation by working with agencies whose primary missions are other than wildlife conservation; 4) recognize the importance of private lands and role of private landowners; 5) take advantage of opportunities to involve academic institutions in conservation; 6) acknowledge skills and contributions of colleagues or coworkers, and fully use those talents; and 7) develop and maintain personal attitudes that enhance working relationships and build on past successes. Application of these recommendations likely will enhance the effectiveness of conservation of wild sheep, and for other species of North American wildlife as well. © 2018 The Wildlife Society.